Genotype, echocardiography, and survival in familial transthyretin amyloidosis. (December 2013) - Arruda-Olson, Adelaide M.; Zeldenrust, Steven R.; Dispenzieri, Angela; Gertz, Morie A.; Miller, Fletcher A.; Bielinski, Suzette J.; Klarich, Kyle W.; Scott, Christopher G.; Grogan, Martha
Abstract Background: More than 100 transthyretin (TTR) variants have been identified which cause familial systemic amyloidosis. It has been increasingly recognized that TTR variants of familial systemic amyloidosis contribute to clinical characteristics, including age at diagnosis, cardiac phenotype and survival. Methods: Two hundred and eighty-two patients who underwent genotyping for TTR variants were identified. This study focused on 116 patients representing the three most common TTR variants; T60A (n = 58), V30M (n = 37) and V122I (n = 21). The remaining subjects (n = 61) were distributed amongst 33 different genotypes and excluded from analysis. Results: Age at diagnosis was similar by genotype. Septal, posterior wall thickness, right ventricular systolic pressure and left ventricular mass index were greater and LVEF lower in the V122I subgroup. At mean follow up of 3.0 ± 2.6 years there were 62 deaths. V30M patients had the best survival. Survival was similar between V122I and T60A patients. The association of genotype with mortality persisted after adjustments for clinical variables. Conclusions: For familial TTR amyloidosis cardiac involvement is frequent and mortality high for T60A, V122I and V30M genotypes. Specific genotype predicted severity of phenotypic expression as measured by echocardiography and survival.